2000
DOI: 10.1093/geront/40.4.397
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Design of Environments for People With Dementia

Abstract: Design of the physical environment is increasingly recognized as an important aid in caring for people with dementia. This article reviews the empirical research on design and dementia, including research concerning facility planning (relocation, respite and day care, special care units, group size), research on environmental attributes (noninstitutional character, sensory stimulation, lighting, safety), studies concerning building organization (orientation, outdoor space), and research on specific rooms and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
376
0
30

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(415 citation statements)
references
References 81 publications
9
376
0
30
Order By: Relevance
“…[25] A dementia-specific environment may serve as therapeutic instrument [50] as well as a means for orientation and promotion of social interaction. [51] Its deficit-compensating effect can help improve the QoL of PwD. [25] However, insufficient QoL of PwD in long-term care facilities is often caused by a lack of staff resources, insufficient training or insufficient social competencies of the carers.…”
Section: Discussionmentioning
confidence: 99%
“…[25] A dementia-specific environment may serve as therapeutic instrument [50] as well as a means for orientation and promotion of social interaction. [51] Its deficit-compensating effect can help improve the QoL of PwD. [25] However, insufficient QoL of PwD in long-term care facilities is often caused by a lack of staff resources, insufficient training or insufficient social competencies of the carers.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the built environment on dementia care outcomes Previous research has demonstrated: the importance of physical environments on the QoL of people living with dementia (Kovach et al, 1997;Lawton, 1997;Brod et al, 2000;Day et al, 2000;Calkins, 2004;Reimer et al, 2004); and that physical environment design features can be associated with quality of care, and behavioural and clinical outcomes (Kovach et al, 1997;Marshall et al, 1999;Day et al, 2000;Devlin and Arneill, 2003;Gitlin et al, 2003;Zeisel et al, 2003;Calkins, 2009). Research has related the built environment and its design features to most dementia related symptoms.…”
Section: Indirect Costsmentioning
confidence: 99%
“…Furthermore, using higher intensity ambient bright light and offering a view outside is very likely to improve the day-night rhythm and orientation in time for residents (Day et al 2000, Thorpe et al 2000, van Hoof et al 2009), especially for those who reside in the central hall. In addition, the staff could look for ways to better delineate structuring activities, such as the organisation of serving the meals.…”
Section: Small and Medium Interventionsmentioning
confidence: 99%